Welcome remarks of signing ceremony memorandum of understanding (MoU) between Universiti Teknologi MARA (UiTM) and University of Portsmouth (UoP) United Kingdom / Prof. Datuk Ts. Dr. Roziah Mohd Janor - Mohd Janor, Roziah (2023)
A very warm welcome and Selamat Datang to all eminent guests to the signing of the Memorandum of Understanding between Universiti Teknologi MARA (UiTM) and the University of Portsmouth (UoP). I am beyond thrilled and optimistic about the wonderful possibilities that can be derived from this historic partnership. UiTM is well informed of UoP's strong academic reputation and its strong commitment to creating an even stronger international academic presence.